Universality and utopia : the 20th century indigenista Peruvian tradition - Sacilotto, Daniel (Anthem studies in Latin American literature and culture., 2023)
This work examines the evolution of the Peruvian indigenista literary tradition in the twentieth century in its relation to the evolution of socialist thought and dialectical materialist philosophy.